2020
DOI: 10.1038/s41598-020-76349-y
|View full text |Cite
|
Sign up to set email alerts
|

Amylase quantification in the terminal Ileum following formation of an Ileostomy

Abstract: Amylase is elevated in the foregut and has been used to confirm anastomotic integrity after pancreatic surgery. The physiological activity of pancreatic enzymes in the ileum has been studied in healthy volunteers but not quantitated with the simple and readily available amylase measurements employed with serum tests. We aim to quantitate the levels of amylase in the terminal ileum. This was a prospective, non-randomised, non-blinded, consecutive cohort study conducted at the Royal Brisbane and Women’s Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…8 A study from our institution measured luminal amylase levels from newly created ileostomies and found the contents of the distal small intestine to be very high in this enzyme (median levels of 4470 to 23,000 U/L at postoperative days 1 to 5). 9 A subsequent pilot study from our institution assessed drain fluid amylase (DFA) in 13 patients undergoing restorative proctectomy (RP) with an ileal pouch. 8 There was a significant rise in DFA on the day of AL in the 2 patients who experienced an AL (p = 0.03).…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
See 1 more Smart Citation
“…8 A study from our institution measured luminal amylase levels from newly created ileostomies and found the contents of the distal small intestine to be very high in this enzyme (median levels of 4470 to 23,000 U/L at postoperative days 1 to 5). 9 A subsequent pilot study from our institution assessed drain fluid amylase (DFA) in 13 patients undergoing restorative proctectomy (RP) with an ileal pouch. 8 There was a significant rise in DFA on the day of AL in the 2 patients who experienced an AL (p = 0.03).…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
“…A study from our institution measured luminal amylase levels from newly created ileostomies and found the contents of the distal small intestine to be very high in this enzyme (median levels of 4470 to 23,000 U/L at postoperative days 1 to 5). 9…”
mentioning
confidence: 99%
“…The measurement of drain fluid amylase or drain fluid Gastrografin may achieve this end and there is emerging evidence of their utility as sensitive BMs for early AL. [17][18][19][20][21] Patients without a TDI are likely to present more dramatically and earlier in their post-operative recovery.…”
Section: Does An Ileostomy Cover the Surgeon Or The Anastomosis?mentioning
confidence: 99%
“…With omitting a TDI comes an imperative to identify AL at its earliest stage and address its management aggressively. The measurement of drain fluid amylase or drain fluid Gastrografin may achieve this end and there is emerging evidence of their utility as sensitive BMs for early AL 17–21 . Patients without a TDI are likely to present more dramatically and earlier in their post‐operative recovery.…”
mentioning
confidence: 99%
“…A pilot study of 13 ileal pouch patients suggested that drain fluid amylase might be a sensitive BM of AL [35]. The authors demonstrated high intra-luminal levels of amylase in the ileum [36] and considered peritoneal levels above the established serum reference range as indicative of AL. They set an amylase value of 130 U/L as their threshold.…”
Section: Registered Trials Of Drain Fluid Biomarkersmentioning
confidence: 99%